Ocena poziomu i jakości życia w funkcjonalnych rejonach obszarów wiejskich Dolnego Śląska - Adamska, Hanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the article, the level and quality of life were showed as a main aim of sustainable development. The detailed analysis was conducted in the functional regions of Lower Silesia, using statistical office data. The investigations showed the most profitable conditions of level and life quality in Kostomłoty, Udanin, and Malczyce communes located in intensive agriculture region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 62-67